2018
DOI: 10.1182/blood-2017-12-820985
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic Rag1 mutations alter the preimmune repertoire at early stages of lymphoid development

Abstract: Hypomorphic mutations allowing residual T- and B-cell development have been found in patients presenting with delayed-onset combined immune deficiency with granulomas and/or autoimmunity (CID-G/AI) and abnormalities of the peripheral T- and B-cell repertoire. To examine how hypomorphic mutations affect the earliest stages of lymphocyte development, we used CRISPR/Cas9 to generate mouse models with mutations equivalent to those found in patients with CID-G/AI. Immunological characterization showed partial devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…T reg abnormalities are also an important factor that may contribute to autoimmune manifestations in RAG deficiency. Reduced number of thymic T reg and a restricted repertoire of peripheral T reg cells have been reported both in patients and in Rag mutant mice . Moreover, we have shown that T reg from patients with OS, AS, and CID‐G/AI have reduced suppressive activity .…”
Section: Abnormalities Of Central and Peripheral T‐cell Tolerancementioning
confidence: 53%
See 4 more Smart Citations
“…T reg abnormalities are also an important factor that may contribute to autoimmune manifestations in RAG deficiency. Reduced number of thymic T reg and a restricted repertoire of peripheral T reg cells have been reported both in patients and in Rag mutant mice . Moreover, we have shown that T reg from patients with OS, AS, and CID‐G/AI have reduced suppressive activity .…”
Section: Abnormalities Of Central and Peripheral T‐cell Tolerancementioning
confidence: 53%
“…High‐throughput sequencing of the Trb repertoire in DN4 thymocytes from Rag1 R972Q and Rag1 F971L mice has revealed skewed usage of V and J genes, with a pattern that was consistent between the two models . Similarly, these mutant mice presented skewed usage of IghV and IghJ genes in pro‐B cells.…”
Section: Abnormalities Of Central and Peripheral T‐cell Tolerancementioning
confidence: 89%
See 3 more Smart Citations